Jordan : Overview of Tobacco Use, Tobacco Control Legislation, and Taxation - World Bank Group (World Bank, Washington, DC, 2019)
This brief provides an overview of tobacco control legislation, use, and taxation in the country. The prevalence of smoking is rather high in Jordan. The Global Adult Tobacco Survey (GATS) found that in 2011, 42.2 percent of people (55.9 percent of men and 23.7 percent of women) aged 15 and above in Jordan smoked tobacco. Among those who smoked tobacco, 35.2 percent smoked cigarettes, and 15.2 percent smoked water-pipe. Smoking cost the country 1 billion Jordanian dinars (JD) in 2012, including money spent on tobacco and smoking-related diseases, which amounted to approximately 5 percent of the gross domestic product. Jordan adopted the National tobacco control strategy for 2017-2019, which is based on the implementation of the WHO's MPOWER strategy, a comprehensive set of tobacco control measures. The strategy seeks to decrease tobacco use by 30 percent by 2025. While most consumed tobacco products in Jordan are manufactured within the country, consistent data on the production of cigarettes and other tobacco products is not available. According to the estimates based on the results of the household surveys, in 2003-2013, tobacco consumption in Jordan increased by 58 percent. In 2010-2013, estimated annual cigarette sales were about 8 billion cigarettes. Till 2014, Jordan had mixed tobacco excise system with specific tax and ad valorem tax, which was changed to tier specific excise system. The main unified specific excise tax gradually increased from 0.42JD per pack in 2014 to 0.57JD in 2018, or by 36 percent in four years. The additional tiered specific excise tax has different rates depending on cigarette price. Tobacco excise revenue in Jordan increased from 312 million JD in 2012 to 554 million JD in 2016. So, the tobacco taxation policy was beneficial for government coffers. However, in 2019 the taxes on cigarettes were not increased. In May 2019, the government imposed a 200 percent tax on electronic cigarettes, vapes, and their paraphernalia. Tobacco price increase in 2010-2016 was rather moderate, and tobacco affordability almost did not change. Such a situation was partly caused by the pricing policy of the tobacco industry. In 2013, to encourage cigarette consumption within the country, the tobacco industry even decreased cigarette prices. In 2017 and 2018, tobacco price increase was substantial, the reduction in tobacco affordability was large enough, and this has the potential to cause a decrease in tobacco consumption. The following recommendations can support the implementation of the National tobacco control strategy by means of both reducing the tobacco consumption and increasing the government revenue: excise rates for cigarettes, water-pipe tobacco, and other tobacco products should be annually increased by at least 20 percent to ensure tobacco affordability reduction, tobacco use surveillance and monitoring should be further strengthened in Jordan, including a regular collection and public presentation of information on sales of cigarettes and other tobacco products, their prices as well as other economic indicators, effective policies to counteract tobacco smuggling and other kinds of illicit tobacco sales should be implemented in line with the provisions of the FCTC Protocol to Eliminate Illicit Trade in Tobacco Products, which is recommended to be ratified by the country.